Finite size effects on the electrical properties of sol-gel synthesized CoFe2O4 powders: deviation from Maxwell-Wagner theory and evidence of surface polarization effects - George, Mathew; Nair, Swapna S.; Malini, K. A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Physics D-Applied Physics, 2007)
Fine particles of cobalt ferrite were synthesized by the sol-gel method. Subsequent heat treatment at different temperatures yielded cobalt ferrites having different grain sizes. X-ray diffraction studies were carried out to elucidate the structure of all the samples. Dielectric permittivity and ac conductivity of all the samples were evaluated as a function of frequency, temperature and grain size. The variation of permittivity and ac conductivity with frequency reveals that the dispersion is due to Maxwell-Wagner type interfacial polarization in general, with a noted variation from the expected behaviour for the cold synthesized samples. High permittivity and conductivity for small grains were explained on the basis of the correlated barrier-hopping model.

Enhanced shape anisotropy and magneto-optical birefringence by high energy ball milling in NixFe1-xFe2O4 ferrofluids - Nair, Swapna S.; Xavier, Francis; Joy, Pattayil Alias; Kulkarni, S. D.; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2008)
Ferrofluids belonging to the series NixFe1-xFe2O4 were synthesised by two different procedures-one by standard co-precipitation techniques, the other by co-precipitation for synthesis of particles and dispersion aided by high-energy ball milling with a view to understand the effect of strain and size anisotropy on the magneto-optical properties of ferrofluids. The birefringence measurements were carried out using a standard ellipsometer. The birefringence signal obtained for chemically synthesised samples was satisfactorily fitted to the standard second Langevin function. The ball-milled ferrofluids showed a deviation and their birefringence was enhanced by an order. This large enhancement in the birefringence value cannot be attributed to the increase in grain size of the samples, considering that the grain sizes of sample synthesised by both modes are comparable; instead, it can be attributed to the lattice strain-induced shape anisotropy(oblation) arising from the high-energy ball-milling process. Thus magnetic-optical (MO) signals can be tuned by ball-milling process, which can find potential applications. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: birefringence; Co-precipitation; ferrofluid; HEBM

Contact potential induced enhancement of magnetization in polyaniline coated nanomagnetic iron oxides by plasma polymerization - Sethulakshmi, N.; Sooraj, V.; Sajeev, U. S.; Nair, Swapna S.; Narayanan, T. N.; Joy, Lija K.; Joy, Pattayil Alias; Ajayan, Pulickel M.; Anantharaman, Maliemadom R. (Applied Physics Letters, 2013)
The present work derives motivation from the so called surface/interfacial magnetism in core shell structures and commercial samples of Fe3O4 and gamma Fe2O3 with sizes ranging from 20 to 30 nm were coated with polyaniline using plasma polymerization and studied. The High Resolution Transmission Electron Microscopy images indicate a core shell structure after polyaniline coating and exhibited an increase in saturation magnetization by 2 emu/g. For confirmation, plasma polymerization was performed on maghemite nanoparticles which also exhibited an increase in saturation magnetization. This enhanced magnetization is rather surprising and the reason is found to be an interfacial phenomenon resulting from a contact potential. (C) 2013 AIP Publishing LLC.